Key Performance Indicators in local government in Poland - Kowalczyk, Magdalena (Research Papers of Wrocław University of Economics, 2018)
One of the basic accusations against public finance units, including local governments (lg), is the lack of economic efficiency and relations of the expenditures and outcomes. Just like in the case of commercial entities, local governments put more emphasis on the possibility to present the effectiveness of their operations not only by means of financial indicators. The herein study constitutes an attempt to demonstrate the possibilities and benefits of introducing the Key Performance Indicators (KPI) reporting in lg. According to the conducted research it results that the use of KPI in order to report on the achieved outcomes in different fields of activities is fully reasonable in terms of local governments. The elaboration of a set of common KPI for all the units shall facilitate the comparison of the achieved results both in time and space. The article presents a new issue that are the opportunities of using KPI in the Polish local governments in order to prepare reports
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 503, s. 236-245
Keywords: key performance indicators; local government units; performance measurement; jednostki samorządu terytorialnego; mierniki efektywności